Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Alpha Au2S nanoparticles: fungal-mediated synthesis, structural characterization and bioassay - Syed, Asad; Al Saedi, Marzouq H.; Bahkali, Ali H.; Elgorgan, Abdallah M.; Kharat, Mahesh; Pai, Kalpana; Pichtel, John; Ahmad, Absar (Green Chemistry Letters and Reviews, 2022)
Luminescent nanoparticles synthesized via bio-based protocols that generate nanoparticles having different chemical compositions along with other functionalities (size and morphology) have received huge attention. We have focused our research on gold sulfide nanoparticles (Au2S NPs) and have biosynthesized these NPs using the fungus Humicola sp. The nanoparticles were characterized by Transmission Electron Microscopy, which showed spherical morphology of Au2S. UV-Visible-NIR spectrophotometry, luminescence spectrophotometry, Selected Area Electron Diffraction, Energy Dispersive Analysis of X-rays, and X-ray diffraction were performed. FTIR confirmed that the fungal metabolites including biomolecules secreted in the reaction medium are primarily responsible for nanoparticle synthesis and stabilization. The fungus reduced the precursor solution (HAuCl4 and Na2SO3) and at the same time capped them with secreted biomolecules. The anti-leishmanial activity of Au2S NPs was determined against L. donovani promastigote (Ag83 strain). Au2S NPs displayed less cytotoxicity towards both normal and cancer (Daudi, ZR-75-1) cell lines. Hemocompatibility was determined via hemolysis assays. This novel fungal-based system demonstrates an economical and environmentally benign process for biosynthesis of Au2S nanoparticles which may find application in bioimaging and labeling studies.
Keywords: Biosynthesis; Cytotoxicity; Gold sulfide; Hemolysis; humicola sp; promastigote